Me before you - Moyes, Jojo, 1969- (New York : Viking, 2012)
Louisa Clark takes a job working for Will Traynor, who is wheelchair bound after a motorcycle accident. When she learns that Will has shocking plans, she sets out to show him that life is still worth living.
"Pamela Dorman Books."
Keywords: Young women -- Fiction; Paraplegics -- Fiction; Love stories